How to get by with half a loop – An investigation of visual and auditory codes in a case of impaired phonological short-term memory (pSTM). (March 2019) - Tree, Jeremy J.; Playfoot, David
Abstract: In the field of cognitive neuropsychology of phonological short-term memory (pSTM), a key debate surrounds the issue of how impairment on tasks deemed to tap this system imply a dissociable phonological input and output buffer system, with the implication that impairments can be fractionated across disruption to separate functional components (Nickels, Howard & Best, 1997). This study presents CT, a conduction aphasic who showed no impairment on basic auditory discrimination tasks, but had very poor nonword repetition. Clear-cut examples of such cases are very rare (see Jacquemot, Dupoux & Bachoud-Levi, 2007), and we interpret the case with reference to a pSTM model that includes input and output buffers. The dissociation between performance on auditory phonological tasks and visual phonological tasks we interpret as consistent with disruption to the link from input buffer to output buffer without concurrent damage to connections from output to input. Previous research has also shown that patients with impairments of pSTM can make visual confusions with orthographically presented items in tasks seeking to tap this mechanism (Warrington & Shallice, 1972), which might stem from having an incomplete pSTM loop. In light of this we examined whether CT's ability on tests of ISR was affected by visual orthographic similarity among list items, and this is indeed what we observed. On balance then, CT's overall profile is considered best interpreted with respect to a dual buffer pSTM model (e.g., Vallar & Papagno, 2002).